2021
DOI: 10.1002/pc.26164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of water absorption on thermomechanical and viscoelastic properties of flax‐hemp‐reinforced hybrid composite

Abstract: The recent development of natural fiber-reinforced polymer composites have shown innumerable economic and environmental benefits for a vast array of engineering applications. It is quintessential to investigate the effect of water absorption on the composites that remain in the water for a maximum of their intended service period. This study is an effort in this direction that investigates the effect of water absorption on thermo-mechanical properties of flaxhemp-reinforced epoxy composites fabricated using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 68 publications
(119 reference statements)
5
27
0
1
Order By: Relevance
“…Storage modulus initially showed a slight drop as the temperature increased, and then a rapid drop in the glass transition region. Similar behaviors and results are observed in studies in the literature 55–57 . While the storage modulus of pure epoxy at room temperature is 2.5 GPa, the storage modulus of nanocomposites with content 0.1 and 0.5% f‐GNF is 3.3 and 3.8 GPa, respectively.…”
Section: Simulation Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Storage modulus initially showed a slight drop as the temperature increased, and then a rapid drop in the glass transition region. Similar behaviors and results are observed in studies in the literature 55–57 . While the storage modulus of pure epoxy at room temperature is 2.5 GPa, the storage modulus of nanocomposites with content 0.1 and 0.5% f‐GNF is 3.3 and 3.8 GPa, respectively.…”
Section: Simulation Results and Discussionsupporting
confidence: 88%
“…Similar behaviors and results are observed in studies in the literature. [55][56][57] While the storage modulus of pure epoxy at room temperature is 2.5 GPa, the storage modulus of nanocomposites with content 0.1 and 0.5% f-GNF is 3.3 and 3.8 GPa, respectively. By adding 0.1 and 0.5 wt.% f-GNF to pure epoxy, molecular mobilization of epoxy chains was prevented, a better resistance was created and an increase of 32% and 52%, respectively, was observed in the storage modulus.…”
Section: Simulating Of Storage Modulus Of Graphene-epoxy Nanocompositesmentioning
confidence: 99%
“…The addition of PPSA increases the modulus values in EP and shows that the addition of PPSA resulted in higher storage modulus compared with pure EP because it may enhance the bonding between PPSA and EP 36–39 . As the temperature increases, the values of storage modulus gradually decreases due to the close packing of the molecules becomes weak and the increases in the molecular mobility 40,41 …”
Section: Resultsmentioning
confidence: 97%
“…[36][37][38][39] As the temperature increases, the values of storage modulus gradually decreases due to the close packing of the molecules becomes weak and the increases in the molecular mobility. 40,41 E" is the measurement of released heat energy per cycle and decided by the molecular motion. 42 Owing to the glass-rubber transition of EP, a maximum of E" and tan δ are reached (Figure 4b,c) followed by a drop as the temperature increases, which is related to the energy dissipation by chain movement in high temperature.…”
Section: Thermomechanical Propertymentioning
confidence: 99%
“…The water swelling rate and biodegradation rate of the composite scaffolds are important factors in determining cell adhesion and proliferation. 35,36 At the same time, the higher the water swelling rate is, the stronger its ability to absorb exudate. The results showed that (Figure 5(a)) with increasing GO content, the water swelling rate of the composite scaffold materials also increased, and compared with the 0% GO content, the water swelling rate of the composite scaffolds with GO contents of 0.5% and 1% increased significantly.…”
Section: Water Swelling Rate and Degradation Ratementioning
confidence: 99%